Comparison of simultaneous bilateral CI surgery vs. sequential CI surgery regarding operative time, perioperative morbidity, and anesthesia risk in children - Fries, Leonie; Everad, Friederike; Beck, Rainer Linus; Aschendorff, Antje; Arndt, Susan; Ketterer, Manuel Christoph (Frontiers in Neurology, 2025)
ObjectivesIn recent years, simultaneous bilateral cochlear implantation (CI) has become the preferred procedure for children with bilateral deafness. The aim of this study is to compare simultaneous bilateral implantation with sequential bilateral CI concerning duration of surgery and anesthesia, perioperative morbidity, mortality, and anesthesia risk.MethodsA retrospective data analysis was conducted on 132 children who were implanted between 2019 and 2024 and aged under 10 years at the time of either simultaneous or second CI. The age at implantation, duration of surgery and anesthesia, anesthesia risk, perioperative morbidity and mortality were compared between the simultaneous and the sequential implantation cohorts.ResultsSimultaneous bilateral CI demonstrated a significant reduced duration of anesthesia in total for both sides (simultaneous CI: 221.7 ± 41.4 min; sequential CI: 262.3 ± 37.11 min, p < 0.0001) and a significant shorter duration of surgery with a mean of 108.6 min (±38.2 min) for both sides in simultaneous CI and 132.7 min (±36.85 min) for sequential CI (p < 0.0001). However, perioperative morbidity and mortality as well as anesthesia risk showed no significant differences. The cumulative duration of hospitalization was significantly longer for sequential CI (simultaneous CI: 5 ± 0.76 days; sequential CI: 10 ± 0.85 days).ConclusionThe study underlines the benefits of simultaneous bilateral CI, regarded as the gold standard, particularly concerning reduced duration of surgery and anesthesia time. In an era of healthcare cost efficiency, simultaneous CI also enables shorter hospital stays. However, the absence of significant differences in perioperative morbidity, mortality, and anesthesia risks must be considered. This makes sequential CI a viable treatment alternative and allows for an individualized treatment approach that accounts for existing comorbidities and individual patient and parental factors.